O projeto de arquitetura de espaços temporários com o uso de sistema construtivo remontável: um estudo exploratório - Albuquerque, Glauce Lilian Alves de (2013)
The purpose of this research is to study the portable or reassemblable architectures, which, different from conventional architecture (whose designs are of permanent buildings), corresponds to the designing of spaces with temporary purposes. The focus of the study is the architectural design of spaces that are produced from building systems that can to be moved to different places (process of assembly / disassembly / reassembly) in order to identify the types of spaces generated and the processes used in their design / projecting. The aim is to investigate relationships between the initial project conceived based on a Reassemblable Construction System (RCS) and its application in the architectural design of professionals and students in order to contribute to the understanding of the specificities of this type of design activity. To this end it was developed the exploratory research based on multimedia methods, which includes: documentary analysis, technical visits, interviews, surveys, academic exercise and documentation by images. Although the study is not conclusive, the results indicate significant differences between the point of view of the RCS´s designers and its users (architects and architecture students) since the users demonstrated to have some difficulty to access the features provided for the first group, in particular the students. It is also demonstrated that the use of RCSs seems to change the appreciation / hierarchization of the conditions of project design, since, unlike what happens in traditional architectural design, the designers who use them seem to be more concerned with constructive issues, especially the structural elements (support and covering), instead of functionality, aesthetics and even physical characteristics of the site